Determination of Hydroxymethylfurfural (HMF) in Honey Based on p-Toluidine as a Reagent Using Spectrophotometric Method - Mashri Ahmad Yahia,; Musa Ahmad,; Lee Yook Heng; Che Wan Zanariah Che Wan Ngah (Trans Tech Publications, Switzerland, 2024)
Spectrophotometric determination of hydroxymethylfurfural (HMF) based on p-toluidine as a reagent has been studied. The absorption intensities were measured at a wavelength range of 250 to 500 nm to record the absorption spectra before and after reaction with the HMF. The solution response was obtained at pH 3. The concentration of HMF was 5 × 10-3 M, whereas for p-toluidine was 8 × 10-3 M .The relative standard deviation (R.S.D.) of reproducibility was 3.33% when concentration of p-toluidine 3 × 10-3 M was used .The photostability was found to be good with 1.9 %. M was used . The photostability was found to be good with 1.9 %.